THE ROLE OF ISLAMIC FINANCIAL SOCIALIZATION IN SHAPING COMMUNITY INTEREST IN CHOOSING ISLAMIC BANKS - Kamil, Insanul; Iswandi, Lalu Muhammad; Fathurrazak, (Jurnal Syarikah : Jurnal Ekonomi Islam, 2025)
This study aims to analyze the role of Islamic financial socialization in influencing public interest in choosing Islamic banks, with a case study of the community in Keruak traditional market, East Lombok. The background of this research lies in the relatively low level of Islamic financial literacy among traditional traders, despite the fact that Islamic banks offer products and services in accordance with Sharia principles and can serve as an alternative financial solution for the community. The research employed a qualitative approach, using data collection techniques such as observation, in-depth interviews, and documentation. The collected data were then analyzed descriptively to illustrate how socialization contributes to shaping public understanding and interest. The findings reveal that the socialization of Islamic finance carried out by Bank NTB Syariah plays a crucial role in enhancing people’s understanding of Sharia principles, benefits, and Islamic banking products. Socialization strategies are implemented through family-based approaches, printed media such as brochures, and digital platforms, including websites and social media. These efforts have proven effective in attracting the interest of traditional market traders to become more aware of, and consider using, Islamic banking services. Nevertheless, several inhibiting factors reduce the effectiveness of socialization, such as low levels of Islamic financial literacy, limited access to Islamic financial institutions, and the strong dominance of conventional banks. These findings highlight the urgent need for structured, intensive, and continuous socialization programs so that Islamic banks can expand their penetration, particularly in traditional markets as the center of people’s economic activities.